Investigation of the phytochemistry and biological activity of isoquinoline alkaloids isolated from the South African medicinal plants, cyrtanthus sanguineus (Lindl.) walp. and cyrtanthus obliquus (L.f.)ait - Brine, Natalie Dawn (Division of Clinical Pharmacology, 2014)
Bibliography: p. 128-140.